Potential remedies for gout from medicinal plants - Jamal, Parveen; Azmi, Saiful Mohammad Nizam; Amid, Azura (IIUM Press, 2011)
Malaysia has diveJ'Sity of medicinal plants and some ofthcm have the property to inhibilxanthine oxidasc (XO). which can be introduced as a ncw natural source of gout medication amI a substitute for synthetic xanthine oxidase inhibitors {XOII. [n this study. thc lea,'es from twemy planl species wcre examined for inhibition of XO. Selection of plams was based on their frequent usages by local folks for their medicinal bencfits. The degrec ofXO inhibition was dctermined by measuring llle absorbance pe<.':trophotomctrlcally at 295 nm associated with uric acid formation. Hundred percent of the crode eJ<tracts were found 10 inhibit XO at 100 ).Ig1ml. and 63.33% sllowed greater tilan 50"/0 inllibition. Tile leaves of Gal"ciltia mrmgu)'wllo and Moriltda e/lip/ica have the potemial to be cJ<ploited as an alternativc to allopurinol as lile crudc cxtracts of these plant materials from all three SQlvcnlS. namely. 70% methanol. ethanol and dislilled water. exhibited the highest XO inhibitory activity. The leaves of Al"crrhoo bil'-nrhf. COl"ico p0I'0.ra and S%m"" {ITOp<'rsicllm can also be considered as alternatives to allopurinol as they have dcmonSfrated among the third beSt XO inhibitol)' activity undcr fllcir respective solvcnt systems.